El paradigma positivista, el giro postpositivista y el auge actual de la argumentación jurídica - Abache Carvajal, Serviliano (2019)
In this paper the positivism and postpositivism paradigmes are reviewed, as well as theactual importance of legal reasoning theory, mainly from Josep Aguiló Regla´s position.